Giant Candida Mycetoma in an Ascending Aorta Tubular Graft. Issue 5 (15th August 2013) - Di Benedetto, Giuseppe; Citro, Rodolfo; Longobardi, Antonio; Mastrogiovanni, Generoso; Panza, Antonio; Iesu, Severino; Bossone, Eduardo
Abstract We report the case of a 46‐year‐old male hospitalized for abdominal pain and fever with history of a David procedure followed by an aortic valve replacement due to severe aortic regurgitation. Transesophageal echocardiography (TEE) and computed tomography showed a large mass floating in the aorta. After surgical excision of the vegetation, attached to the Dacron prosthesis, histological examination revealed Candida hyphae and spores confirming the diagnosis of a mycetoma in an ascending aorta tubular graft. At six‐month follow‐up, the patient was in good clinical condition without recurrence of the fungal mass on TEE. doi: 10.1111/jocs.12193 (J Card Surg 2013;28:557–560)